Development of a documentation instrument for the conservative treatment of spinal disorders in the International Spine Registry, Spine Tango - Kessler, J.; Melloh, Markus; Zweig, T.; Aghayev, E.; Röder, C. (2011)
Spine Tango is the first and only International Spine Registry in operation to date. So far, only surgical spinal interventions have been recorded and no comparable structured and comprehensive documentation instrument for conservative treatments of spinal disorders is available. This study reports on the development of a documentation instrument for the conservative treatment of spinal disorders by using the Delphi consensus method. It was conducted with a group of international experts in the field. We also assessed the usability of this new assessment tool with a prospective feasibility study on 97 outpatients and inpatients with low back or neck pain undergoing conservative treatment. The new 'Spine Tango conservative' questionnaire proved useful and suitable for the documentation of pathologies, conservative treatments and outcomes of patients with low back or neck problems. A follow-up questionnaire seemed less important in the predominantly outpatient setting. In the feasibility study, between 43 and 63% of patients reached the minimal clinically important difference in pain relief and Core Outcome Measures Index at 3 months after therapy; 87% of patients with back pain and 85% with neck pain were satisfied with the received treatment. With 'Spine Tango conservative' a first step has been taken to develop and implement a complementary system for documentation and evaluation of non-surgical spinal interventions and outcomes within the framework of the International Spine Registry. It proved useful and feasible in a first pilot study, but it will take the experience of many more cases and therapists to develop a version similarly mature as the surgical instruments of Spine Tango. © Springer-Verlag 2010.